Aesthetic Dentistry, How You Say and How You See: A 500-People Survey on Digital Preview and Color Perception - Zotti F; Pappalardo D; Capocasale G; Sboarina A; Bertossi D; Albanese M (Dove Medical Press, 2020)
Francesca Zotti, Davide Pappalardo, Giorgia Capocasale, Andrea Sboarina, Dario Bertossi, Massimo Albanese Department of Surgical Sciences, Paediatrics and Gynecology, University of Verona, Verona, ItalyCorrespondence: Francesca Zotti Department of Surgical Sciences, Paediatrics and GynecologyUniversity of Verona, P.le L.A. Scuro, 10, Verona 37134, ItalyTel/Fax +39 045 812 6938Email francesca.zotti@univr.itPurpose: Digital technologies have improved ways to perform aesthetic dentistry in the last few years. The aims of this survey were to investigate the most preferred way to preview the result of an aesthetic dental rehabilitation among a population of dental professionals and laypeople and to compare aesthetic standards of the general population and dentists in terms of the color of teeth for aesthetic dental rehabilitations.Patients and Methods: A questionnaire was sent to the subjects (dentists and laypeople) during a 1-year period and, together with their demographic data, different ways to preview the result of an aesthetic rehabilitation were submitted, such as digital smile design, dental wax-up and oral explanation. Furthermore, an additional section of the questionnaire investigated the most suitable color for an aesthetic rehabilitation based on the colors of the VITA Scale. Results were statistically analyzed (with Chi-square of independence and Mann–Whitney U-test) highlighting differences of answers based on age groups, educational attainment, gender, and belonging or not to the dental field.Results: Findings showed that digital smile design (digital preview) is a high-appreciated method for previewing and communicating with patients both by dental professionals and laypeople. Furthermore, lighter colors were found to be more valued by laypeople and significant differences were highlighted between the two populations assessed.Conclusion: It seems to be viable to use digital preview for dentists and laypeople to improve previewing and communicating ways. It might be advisable to better motivate patients in recognizing aesthetical features and to raise their awareness in preferring more mimetic aesthetic results. Great opportunities are opened up by digital smile design in teaching, learning, and routine practice.Keywords: digital smile, patient communication, aesthetic colours, aesthetical idea, digital dentistry